2013
DOI: 10.1126/science.1230911
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Role of Transition Metal Ion Catalysis During In-Cloud Oxidation of SO 2

Abstract: Global sulfate production plays a key role in aerosol radiative forcing; more than half of this production occurs in clouds. We found that sulfur dioxide oxidation catalyzed by natural transition metal ions is the dominant in-cloud oxidation pathway. The pathway was observed to occur primarily on coarse mineral dust, so the sulfate produced will have a short lifetime and little direct or indirect climatic effect. Taking this into account will lead to large changes in estimates of the magnitude and spatial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
303
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(330 citation statements)
references
References 83 publications
15
303
0
1
Order By: Relevance
“…The model's underestimation during the severe winter haze episodes is consistent with previous studies (Liu et al, 2010;Zhou et al, 2014). Possible reasons for this underestimation are (1) the bias in simulating meteorological conditions during haze episodes; (2) un- certainties in emissions; (3) missing SOA in the MOSAIC mechanism, which will be addressed below; and (4) the lack of formation mechanisms of secondary inorganic aerosols, like heterogeneous oxidation of SO 2 on the surface of particulate matter (Harris et al, 2013). By adjusting SO 2 and NO x emissions according to surface observations and parameterizing the heterogeneous oxidation of SO 2 on deliquesced aerosols in the GEOS-Chem model, Y. X. reported improvements of simulated PM 2.5 spatial distribution and an increase of 120 % in sulfate fraction in PM 2.5 .…”
Section: Pm 25supporting
confidence: 77%
“…The model's underestimation during the severe winter haze episodes is consistent with previous studies (Liu et al, 2010;Zhou et al, 2014). Possible reasons for this underestimation are (1) the bias in simulating meteorological conditions during haze episodes; (2) un- certainties in emissions; (3) missing SOA in the MOSAIC mechanism, which will be addressed below; and (4) the lack of formation mechanisms of secondary inorganic aerosols, like heterogeneous oxidation of SO 2 on the surface of particulate matter (Harris et al, 2013). By adjusting SO 2 and NO x emissions according to surface observations and parameterizing the heterogeneous oxidation of SO 2 on deliquesced aerosols in the GEOS-Chem model, Y. X. reported improvements of simulated PM 2.5 spatial distribution and an increase of 120 % in sulfate fraction in PM 2.5 .…”
Section: Pm 25supporting
confidence: 77%
“…were found to be the most important sources for in-cloud addition of sulfate to mixed particles (the most common particle type during HCCT-2010), while in-cloud aqueous oxidation of SO 2 primarily catalysed by transition metal ions (Harris et al, 2013b) was most important for coarse mineral dust. The isotopic analyses showed that the sulfate content of particles increased following cloud processing during HCCT-2010 by > 10-40 % depending on particle type (cf.…”
Section: Chemical In-cloud Processing Of the Particlesmentioning
confidence: 99%
“…The contribution of anthropogenic and natural Fe-containing particle sources (Moteki et al, 2017) to observed Fe-containing residues is expected. The presence of Fe in the cloud droplets plays an important role in aqueous-phase SO 2 catalytic oxidation in cloud processing (Harris et al, 2013), thus accelerating the sulfate content of Fe-containing particles in cloud processing.…”
Section: The Chemical Characterization Of Cloud Droplet Residuesmentioning
confidence: 99%